1992
DOI: 10.1007/bf00353892
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the ?2-macroglobulin receptor/low density lipoprotein receptor-related protein in human tissues

Abstract: The hepatic alpha 2-macroglobulin receptor (alpha 2MR)/low density lipoprotein receptor-related protein (LRP) binds and endocytoses alpha 2-macroglobulin-proteinase complexes in plasma. In addition, it binds lipoproteins, a novel 40 kDa protein, and complexes between plasminogen activators and plasminogen activator inhibitor type-1. This study shows, for the first time, the tissue distribution of alpha 2MR/LRP as determined by immunohistochemistry with specific monoclonal antibodies. The analysis revealed alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
242
1
5

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(268 citation statements)
references
References 41 publications
19
242
1
5
Order By: Relevance
“…The microwave-oven treatment used by us, moreover, may make antigenic determinants on u-PAR accessible to immunochemical detection, by causing dissociation of u-PA/u-PAR and vitronectin/u-PAR complexes. (r2MR/LRP has not hitherto been studied immunohistochemically in breast carcinomas, but Moestrup et al (1992) reported fibroblastic staining and absence of epithelial staining in normal human breast tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The microwave-oven treatment used by us, moreover, may make antigenic determinants on u-PAR accessible to immunochemical detection, by causing dissociation of u-PA/u-PAR and vitronectin/u-PAR complexes. (r2MR/LRP has not hitherto been studied immunohistochemically in breast carcinomas, but Moestrup et al (1992) reported fibroblastic staining and absence of epithelial staining in normal human breast tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, both receptors are expressed on antiinflammatory macrophages and co-regulated by glucocorticoids (103,111). However, unlike CD163, the CD91 receptor is expressed on hepatocytes, fibroblasts, and syncytiotrophoblasts in addition to macrophages (110,158). The downstream consequences of heme ingestion in macrophages are not dependent on the mechanism(s) of its delivery to HO-1 (33).…”
Section: Role Of Ho-1 In the Mononuclear Phagocyte Systemmentioning
confidence: 99%
“…While these receptors have overlapping ligand specificity, they exhibit a different pattern of expression. LRP is widely expressed but prominent in liver and brain (52); VLDL receptor in heart, muscle, adipose tissue, and brain (53); glycoprotein 330 is prominently expressed in specialized epithelia of the brain, lung, and kidney (54,55). Recent studies (11,40) indicate that the VLDL receptor is expressed in the endothelium and probably represents the RAP-sensitive receptor responsible for the catabolism of TSP-1 in these cells.…”
Section: Binding Of 125 I-labeled Tsp-1 To Mef At 4°c Is Inhibited Bymentioning
confidence: 99%